Influence of aided audibility on speech recognition performance with frequency composition for children and adults. - Brennan, Marc A.; Browning, Jenna M.; Spratford, Meredith; Kirby, Benjamin J.; McCreery, Ryan W. (International Journal of Audiology, 2021)
The primary purpose of this project was to evaluate the influence of speech audibility on speech recognition with frequency composition, a frequency-lowering algorithm used in hearing aids. Participants were tested to determine word and sentence recognition thresholds in background noise, with and without frequency composition. The audibility of speech was quantified using the speech intelligibility index (SII). Participants included 17 children (ages 6–16) and 21 adults (ages 19 to 72) with bilateral mild-to-severe sensorineural hearing loss. Word and sentence recognition thresholds did not change significantly with frequency composition. Participants with better aided speech audibility had better speech recognition in noise, regardless of processing condition, than those with poorer aided audibility. For the child participants, changes in the word recognition threshold between processing conditions were predictable from aided speech audibility. However, this relationship depended strongly on one participant with a low SII and otherwise, changes in speech recognition between frequency composition off and on were not predicable from aided speech audibility. While these results suggest that children who have a low-aided SII may benefit from frequency composition, further data are needed to generalise these findings to a greater number of participants and variety of stimuli.